2014
DOI: 10.1371/journal.pone.0106531
|View full text |Cite
|
Sign up to set email alerts
|

TripNet: A Method for Constructing Rooted Phylogenetic Networks from Rooted Triplets

Abstract: The problem of constructing an optimal rooted phylogenetic network from an arbitrary set of rooted triplets is an NP-hard problem. In this paper, we present a heuristic algorithm called TripNet, which tries to construct a rooted phylogenetic network with the minimum number of reticulation nodes from an arbitrary set of rooted triplets. Despite of current methods that work for dense set of rooted triplets, a key innovation is the applicability of TripNet to non-dense set of rooted triplets. We prove some theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…This finding has important implications for species tree estimation. Several new methods for estimating species trees from large data sets have used the “rooted triples” method to build trees for subsets of the overall data set, with a second step in which the trees based on triplets are assembled into an overall species tree estimate (Ewing et al, 2008; DeGiorgio and Degnan, 2010; Liu et al, 2010; Poormohammadi et al, 2014). This method is expected to work well in the absence of gene flow, because the rooted triple with the highest probability under the coalescent model is known to be displayed on the species tree (Degnan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This finding has important implications for species tree estimation. Several new methods for estimating species trees from large data sets have used the “rooted triples” method to build trees for subsets of the overall data set, with a second step in which the trees based on triplets are assembled into an overall species tree estimate (Ewing et al, 2008; DeGiorgio and Degnan, 2010; Liu et al, 2010; Poormohammadi et al, 2014). This method is expected to work well in the absence of gene flow, because the rooted triple with the highest probability under the coalescent model is known to be displayed on the species tree (Degnan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When more complex networks are needed (e.g. Fig 8), not restricted algorithms such as NCHB, TripNet, RPNCH and SIMPLISTIC are applicable which try to construct a consistent network with the optimality criterions (the level or the number of reticulation nodes) [6][7][8]16]. Among the above four mentioned algorithms, SIMPLISTIC is not exact and just works for dense sets of triplets while for the other three methods there is no constraint on the input triplets.…”
Section: Plos Onementioning
confidence: 99%
“…Also inner nodes i.e. nodes except root and leaves, has in-degree 1 and out-degree at least 2 [2,7].…”
Section: Definitions and Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,18,19,22]). Even so, it has been observed that the set of triplets displayed by a level-1 network does not necessarily provide all of the information required to uniquely define or encode the network [5].…”
Section: Introductionmentioning
confidence: 99%